Challenge of Humans with Wild-type Salmonella enterica Serovar Typhi Elicits Changes in the Activation and Homing Characteristics of Mucosal-Associated Invariant T Cells - Salerno-Goncalves, Rosângela; Luo, David; Fresnay, Stephanie; Magder, Laurence; Darton, Thomas C.; Jones, Claire; Waddington, Claire S.; Blohmke, Christoph J.; Angus, Brian; Levine, Myron M.; Pollard, Andrew J.; Sztein, Marcelo B. (Frontiers in Immunology, 2017)
Gastrointestinal infections by Salmonella enterica serovar Typhi (S. Typhi) are rare in industrialized countries. However, they remain a major public health problem in the developing world with an estimated 26.9 million new cases annually and significant mortality when untreated. Recently, we provided the first direct evidence that CD8+ MAIT cells are activated and have the potential to kill cells exposed to S. Typhi, and that these responses are dependent on bacterial load. However, MAIT cell kinetics and function during bacterial infections in humans remain largely unknown. In this study, we characterize the human CD8+ MAIT cell immune response to S. Typhi infection in subjects participating in a challenge clinical trial who received a low- or high-dose of wild-type S. Typhi. We define the kinetics of CD8+ MAIT cells as well as their levels of activation, proliferation, exhaustion/apoptosis and homing potential. Regardless of the dose, in volunteers resistant to infection (NoTD), the levels of CD8+ MAIT cells after S. Typhi challenge fluctuated around their baseline values (day 0). In contrast, volunteers susceptible to the development of typhoid disease (TD) exhibited a sharp decline in circulating MAIT cells during the development of typhoid fever. Interestingly, MAIT cells from low-dose TD volunteers had higher levels of CD38 co-expressing CCR9, CCR6, and Ki67 during the development of typhoid fever than high-dose TD volunteers. No substantial perturbations on the levels of these markers were observed in NoTD volunteers irrespective of the dose. In sum, we describe, for the first time, that exposure to an enteric bacterium, in this case S. Typhi, results in changes in MAIT cell activation, proliferation, and homing characteristics, suggesting that MAIT cells are an important component of the human host response to bacterial infection.